Pembangkit Listrik Tenaga Air Pikohidro untuk Kebutuhan Pengembangan Lokasi Wisata Bendungan Desa Menaming Rokan Hulu Riau: Hydroelectric Power Plant Pico Hydro for the needs of the Menaming Village Dam Tourism Location, Rokan Hulu, Riau - Asral, Asral; Fatra, Warman; Handika, Yuli; Pekei, Ferdinandus (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The Menaming Dam is located in Menaming Village, about 3 km away from residential areas, so it is far from the reach of electricity service providers. From the dam, the water is distributed through irrigation canals to the rice fields and fishery and contains hydraulic power, then could be utilized for electricity generation. The location of the dam has attractive views so that it becomes tourism, but there is no electricity available, causing its development to be hindered. Utilization of water resources in irrigation can be done by developing a waterwheel as driving for electricity generators. The power plant with an undershot waterwheel is very suitable to be developed because it is easy to manufacture and maintain. Besides that, the structure and shape can add to the beauty and attractiveness of visitors to tourist sites. Now a hydroelectric power plant has been installed with a total power of about 70 W. Electricity is transmitted using cables through the power poles and an LED light is installed on each of them. Furthermore, in one of the stalls in the tourist location, the installation of lights and sockets for charging mobile phones was made. Lights were also installed in an adjacent house.